Enhancing E-Waste Management Awareness and Campaign in Schools and Communities in the Philippines - Sulisworo, Dwi; Maryani, Ika; Budijati, Siti Mahsanah; Mohammad, Nhelbourne K.; Abdullah, Abdul Jabbar; Ayun, Ummu Qurrota; Hidayah, Nur; Chotijah, Hindun Yafa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to raise awareness and promote ethical e-waste management based on Islamic principles. It seeks to educate students and local communities on the importance of sustainable electronic waste disposal while integrating environmental responsibility with religious values. The study was conducted at Western Philippines University and an Islamic boarding school in Rio Tuba, Palawan, Philippines. It involved educational workshops, field surveys, and collaboration with organizations such as Muhammadiyah Philippines and Palawan Muslim Consultative Da’wah. Due to the hazardous nature of e-waste, hands-on recycling activities were replaced with location assessments for future management projects. The program successfully enhanced students’ understanding of e-waste issues and the ethical responsibility of managing electronic waste. Participants engaged in discussions, site visits, and project planning, fostering a strong commitment to sustainable practices within their communities. This study was limited by the inability to conduct hands-on recycling activities due to safety concerns. Additionally, the research focused on a specific educational setting, which may affect the generalizability of the findings. This study contributes to environmental education, particularly in integrating Islamic values with sustainability efforts. It provides a framework for ethical e-waste management that can be applied in educational institutions and community development programs. The findings are relevant to educators, policymakers, and environmental researchers seeking to promote sustainable waste management through religious and ethical perspectives.